Difficulties in verbalizing emotions in patients with functional neurological disorder: An investigation of the extent of mismatch in self-reported and task-induced emotional responses. - van Dijl, T.L.; Aben, H.P.; Synhaeve, N.E.; de Waardt, D.A.; Videler, A.C.; Kop, W.J. (General Hospital Psychiatry, 2026)
Patients with Functional Neurological Disorder (FND) frequently report difficulties in verbalizing emotions. Evidence suggests a mismatch between patients' self-reports and results from behavioral experiments. The aim of this study is to assess whether self-reported difficulties in verbalizing emotions of patients with FND match potential impairments in verbalizing emotions during structured anger-induction tasks. The Bermond-Vorst Alexithymia Questionnaire - Verbalizing Emotions subscale (BVAQ-VE) was used to assess self-reported difficulties verbalizing emotions. Video recordings of three emotion-inducing tasks that focused on anger were used to measure task-induced difficulties verbalizing emotions. The level of mismatch was calculated by subtracting the percentile score of the task response scores from the percentile score of the BVAQ-VE for each participant. The Mismatch Index was then compared between the FND patient and control groups. Data were available for 55 patients with FND (mixed presentations; mean age = 44.4 [SD = 16.7] years, 63.6% women) and 42 healthy controls (M = 42.2 [SD = 15.5] years, 57.1% women). Patients had higher BVAQ-VE scores (M = 16.9, SD = 6.5) than controls (M = 13.2, SD = 7.4, p =.012, Cohen's d = 0.525). In contrast, patients verbalized emotions just as often as controls during the tasks (U = 1090.5, z = 0.490, p =.624). However, there was no significant difference in the Mismatch Index between patients (M = 0.086, SD = 0.412) and healthy controls (M = -0.035, SD = 0.439, Cohen's d = 0.284, p =.170). This study suggests that patients with FND experience more difficulties verbalizing emotions (the verbal component of alexithymia) than healthy controls, while these difficulties are not elevated in response to anger induction tasks. More research is needed to confirm these findings with emotions other than anger. • FND patients report more difficulty verbalizing emotions than healthy controls. • No group difference found in verbal emotion expression during anger-related tasks. • There was no significant mismatch between self-reported difficulty and task results.